Mamluk administration in Aleppo in the ninth century AH / fifteenth century AD (the case of Banu Saffah) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Aleppo has enjoyed great importance in the age of the Mamluk Empirecircassian because of the importance of its geographical location on the northern border of the state Mamluk. Aleppo was an administrative point of central authority in the city of Cairo. This study aims to demonstrate the military and civilian administrative functions, which are found in the city, and groups that have held these jobs. In addition to addressing possible means in order to get, a job in this age.